Answer:
its the second one
Step-by-step explanation:
Answer:
c. f(x) x+1/x-1
Step-by-step explanation:
To answer this question, we need to check each answer one by one until we find the right one.
y = (x+6)/(x-6)
switch x and y
x = (y+6)/(y-6)
solve for y
x(y-6) = y+6
xy - 6x = y+6
y(x-1) = 6x+6
y = (6x+6) /(x-1) = 6(x+1)/(x-1)
f^-1(x) = 6(x+1)/(x-1)
y = (x+2)/(x-2)
switch x and y
x = (y+2)/(y-2)
solve for y
x(y-2) = y+2
xy -2x = y+2
y(x-1) = 2x+2
y = (2x+2)/(x-1)
f^-1(x) = 2(x+1)/(x-1)
y = (x+1)/(x-1) ------ correct one
switch x and y
x = (y+1)/(y-1)
solve for y
x(y-1) = y+1
xy - x = y+1
y(x-1) = x+1
y = (x+1)/(x-1)
f^-1(x) = (x+1)/(x-1)
f(x) = f^-1(x)
Answer:
Step-by-step explanation:
<u>Sum of (7x+4) and the opposite of 7x:</u>
- 7x + 4 + (-7x) =
- 7x + 4 - 7x =
- 4
Answer:
1 2⋅−1⋅3 5=4 5
Step-by-step explanation:
Combine multiplied terms into a single fraction
12y−1⋅35=45
\frac{1}{2}y-1 \cdot \frac{3}{5}=\frac{4}{5}
21y−1⋅53=54
12−1⋅35=45
I think it’s .75¢ because $6.75 + $2.50 = $9.25